Descriptive analysis of theory examination question papers of 2nd MBBS pharmacology of Krantiguru Shamji Krishna Verma Kachchh University (Gujarat) - Khuteta, Neelesh K.; Saurabh, Manoj K. (International Journal of Basic & Clinical Pharmacology, 2016)
Background: The Question Paper is the most important tool of theory exam examination. An attempt was made to assess the pharmacology question papers of university examination in accordance with their guidelines. To assess the pharmacology theory question papers for content validity, area of importance and to test the level of cognitive domain. Methods: Twenty four papers of university comprising 695 questions after preparing 520 learning objective were analysed. All questions were analysed for coverage of different subdivision of Pharmacology and marks allotted to them, type of taxonomic level of each question asked on the basis of verb use and percentage of question asked from area of importance. Results: It was observed that 18.40% weightage of marks given to general pharmacology and least .67% for immunosuppressant in paper I whereas in paper II, 34.90% for antimicrobial agents. About 84% questions were asked from must know area, 8.07% from nice to know area and 7.90 from desirable to know area. In paper I, 92.08% of the questions were to test factual recall (Bloom level I), remaining 07.93% were reasoning type but in other paper verbs were used to test only lower cognitive domain. Conclusions: All the sub-divisions of pharmacology were not covered in each theory assessment. Majority of questions were asked to test lower level of cognitive domain. Theory question papers should be designed to give proper weightage to whole subject area. Blue printing of theory question papers is absolutely necessary.